2015
DOI: 10.1021/es505120s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fulvic Acid Surface Coatings on Plutonium Sorption and Desorption Kinetics on Goethite

Abstract: The rates and extent of plutonium (Pu) sorption and desorption onto mineral surfaces are important parameters for predicting Pu mobility in subsurface environments. The presence of natural organic matter, such as fulvic acid (FA), may influence these parameters. We investigated the effects of FA on Pu(IV) sorption/desorption onto goethite in two scenarios: when FA was (1) initially present in solution or (2) found as organic coatings on the mineral surface. A low pH was used to maximize FA coatings on goethite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Phosphate removal reached a plateau when organic acids concentration was above 100 mg TOC/L. It indicated negligible sites were occupied at low organic acids level and adsorptive sites were not limited for phosphate adsorption (Tinnacher et al, 2015). However, at higher concentration, organic acids of small molecular size, e.g.…”
Section: Characterization Of the Fresh And Preloaded Hzo-201mentioning
confidence: 99%
“…Phosphate removal reached a plateau when organic acids concentration was above 100 mg TOC/L. It indicated negligible sites were occupied at low organic acids level and adsorptive sites were not limited for phosphate adsorption (Tinnacher et al, 2015). However, at higher concentration, organic acids of small molecular size, e.g.…”
Section: Characterization Of the Fresh And Preloaded Hzo-201mentioning
confidence: 99%
“…Yang et al [52] found that the association HA and ZnO enhanced the U(VI) desorption, while HA-SiO 2 or HA-hydrous ferric oxide interactions inhibited U(VI) desorption. Tinnacher et al [53] reported that fulvic acid coated on goethite surface decreased Pu(IV) desorption. The different interaction between HA and minerals might control the desorption of radionuclides from colloidal suspensions, and thereby affected the physicochemical behavior of radionuclides in the natural environment.…”
Section: Effect Of Hamentioning
confidence: 99%
“…Thus, sorbed Pu (IV) can be remobilized as soluble and labile Pu (V) species, which then increase Pu transport and biouptake in aquatic ecosystems (Kaplan et al, 2004;Xu et al, 2014). In addition to the oxidative dissolution of Pu (IV), interactions with naturally-occurring organic matter have critical implications on its sorption and desorption kinetics in the subsurface water environments (Tinnacher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%